การใช้ข้อมูลสารสนเทศทางการบัญชีของผู้ประกอบการธุรกิจสถานีบริการน้ำมันเชื้อเพลิงในจังหวัดเชียงใหม่ - จำเนียร แก้วกันธา (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2017)
The purpose of this independent study was to study the use of accounting information of petrol stations’ entrepreneurs in Chiang Mai. Data were collected by using questionnaires with 118 petrol stations’ entrepreneurs in Chiang Mai or 29.43 percent of the overall population. Data were analyzed by descriptive statistics: frequency, percentage and mean. The results revealed that the petrol stations’ entrepreneurs in Chiang Mai used information for considering petrol purchasing as follows: remaining petrol, petrol price trend, and credit period. In terms of information for pricing arrangement and marketing promotion, there were government policy, cost for purchasing petrol, and sale prices of competitors. Moreover, the study revealed that most of the entrepreneurs used accounting information in the operation. The details of levels for using accounting information for management were described as follows. 1) Planning: entrepreneurs used accounting information for planning at a high level. The highest using averages of accounting information were petrol purchased budget, income of petrol sale, and report of profit - loss statement respectively. 2) Directing: entrepreneurs used accounting information for directing at a high level. The highest using averages of accounting information were daily petrol sold report, daily cash income-expense report, petrol ordered report respectively. 3) Control: entrepreneurs used accounting information for control at a high level. The highest using averages of accounting information were the report of the comparison between previous and present year of financial statement by conducting comparative analysis on numbers of each item and total numbers of the same statement in percentage rate, the report of comparative analysis between actual numbers and budgeted number such as petrol sale, cost of goods sold (petrol), and administrative expenses. In addition, report of operating efficiency analysis by using financial ratio was used. 4) Decision making: entrepreneurs used accounting information for making decision at a high level. The highest using averages of accounting information were the report of petrol cost purchasing for price arrangement, the report about remaining petrol before ordering, and the daily report of the calculation on remaining petrol for inventory management respectively. In terms of problems using accounting information, it was found that entrepreneurs had problems at a medium level. The entrepreneurs confronted with the highest average problem about personnel were not enough to prepare accounting report, personnel lack of experiences in making accounting report, and personnel did not have enough knowledge and ability to make accounting report.